An analysis of the observed low‐level structure of rapidly intensifying and mature hurricane Earl (2010). (12th February 2014) - Montgomery, Michael T.; Zhang, Jun A.; Smith, Roger K.
<x xml:space="preserve">Abstract</x> We examine dynamic and thermodynamic aspects of Atlantic hurricane Earl (2010) during its intensification and mature phases over four days of intensive measurements. During this period, Earl underwent an episode of rapid intensification, maturity, secondary eyewall replacement, re‐intensification and the early part of its decline. The observations are used to appraise elements of a new model for tropical‐cyclone intensification. The results affirm the conventional (vortex interior) and boundary‐layer spin‐up mechanisms that form dynamical elements of the azimuthally averaged view of the new intensification model. The average maximum tangential winds beneath the eyewall are found to exceed the gradient wind by between 20 and 60%. The results suggest also that the gradient wind balance approximation in the low‐level vortex interior above the strong inflow layer may not be as accurate in the inner‐core region of a tropical cyclone during its intensification as has been widely held. An analysis of the low‐level thermodynamic structure affirms the radial increase of moist equivalent potential temperature, θe, with decreasing radius during the intensification process, a necessary ingredient of the new model for maintaining convective instability in the presence of a warming upper troposphere. An unanticipated finding is the discovery of an unmixed boundary layer in terms of θe within several hundred kilometres of the vortex centre. In the inner‐core region, this finding is not consistent with the axisymmetric eruption of the boundary layer into the eyewall unless there are non‐conservative (eddy) processes acting to modify the entropy of ascending air.